Biodegradability of starch nanocomposite films containing different concentrations of chitosan nanoparticles in compost and planting soils - Othman, Siti Hajar; Ronzi, Nur Diana Arisya; Shapi’i, Ruzanna Ahmad; Dun, Mao; Ariffin, Siti Hajar; Mohammed, Mohd Afandi P. (Multidisciplinary Digital Publishing Institute, 2023)
Starch-based nanocomposite films containing chitosan nanoparticles (S/CNP films) are biodegradable and promising alternatives for non-biodegradable synthetic plastics. Nonetheless, limited work has been conducted to investigate the biodegradability of the films in soil. Thus, this work is aimed at investigating the biodegradation of starch-based films containing different concentrations of CNP (0, 10, 15, 20, 25 w/w solid starch) via a soil burial test using compost and planting soils. The biodegradability was investigated in terms of weight loss, visual appearance, morphology, and structural changes. It was found that S/CNP films biodegraded slower than neat starch films, and the degradation rate was reduced by 46 and 44 in compost and planting soils, respectively, with the increase in the concentrations of CNP from 10 to 25 w/w incorporated into the films. The degradation rate of films in compost soil after 8 days was found to be higher (0.0617 g/day) than in planting soil (0.0266 g/day). Visual appearance, morphology, and structural change results also supported these findings. The biodegradable S/CNP films can be used to reduce the usage of synthetic plastic.